2009
DOI: 10.1002/jso.21240
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cutaneous adverse effects of methylene blue dye injection for lymphatic mapping/sentinel lymphadenectomy

Abstract: MB dye may cause cutaneous changes more subtle than previously described. Physicians caring for patients having LM/SL using MB should be aware of these effects so that a proper differential diagnosis can be entertained postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Additional case series have also noted cutaneous manifestations at the site of intraparenchymal injections of methylene blue. In a series of 78 patients receiving peritumoral injections of methylene blue, 11.8% exhibited non-cellulitic inflammatory changes including intense demarcated erythema and telangectasias, which developed within 10 days postoperatively but before the initiation of radiotherapy [15]. The authors concluded that studies of variation in volume and concentration of methylene blue, as well as site of injection, are necessary to clarify the safest use of this tracer for sentinel node identification in the axilla.…”
Section: Methylene Bluementioning
confidence: 99%
“…Additional case series have also noted cutaneous manifestations at the site of intraparenchymal injections of methylene blue. In a series of 78 patients receiving peritumoral injections of methylene blue, 11.8% exhibited non-cellulitic inflammatory changes including intense demarcated erythema and telangectasias, which developed within 10 days postoperatively but before the initiation of radiotherapy [15]. The authors concluded that studies of variation in volume and concentration of methylene blue, as well as site of injection, are necessary to clarify the safest use of this tracer for sentinel node identification in the axilla.…”
Section: Methylene Bluementioning
confidence: 99%
“…Moreover, choosing and using a blue dye are also important for a healthy flap in patients who have planned to undergo sentinel lymph node dissection. The intradermal injection of methylene blue dye, different from isosulfan blue, can cause inflammatory cutaneous adverse effects such as skin erythema, ulcers, and necrosis (33,34). Therefore, isosulfan blue, instead of methylene blue, can be used for sentinel mapping in breast cancer patients scheduled for RF reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…We used isosulfan blue in three patients for sentinel mapping, and we did not encounter any inflammation or perfusion disturbance of the donor tissue. If methylene blue is used for sentinel mapping, an intraparenchymal preparation (5 ml) of a 1% blue dye injection will be much safer to avoid undesirable complications of the flap (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Cases have been described in the literature of tissue necrosis after application of methylene blue dye[27,28] which has been associated with a number of local complications due to its tissue reactive properties. Some authors have therefore suggested replacing methylene blue with an alternative dye.…”
Section: Discussionmentioning
confidence: 99%